The Use of Hyperbaric Oxygen Therapy for Ear Reconstruction: A Case Series - Tulong, Marcella Tirza; Oley, Mendy Hatibie; Oley, Maximillian Christian; Sundoro, Ali; Faruk, Muhammad (Lingkar Studi Bedah Plastik Foundation, 2021)
Introduction: The unique anatomy of the ear makes the reconstruction more challenging. Microtia and auricula hematomas are deformities or defects that can occur in the ear. Treating traumatic injury and congenital malformations of the ears needs some technique and expertise. Hyperbaric Oxygen Therapy is an additional therapy that makes a significant contribution and is effective in wound healing. Case Series: In our first case, a 52-year-old man presented with a traumatic right cauliflower ear due to a traffic accident two weeks before hospital admission. The second case involves a boy 14-year-old who has a Microtia in the right ear with total ear construction performed using autologous costochondral cartilage techniques in a two-stage. Results: Both cases following hyperbaric oxygen therapy, yield good results with good scars, no sign of infection nor tissue necrosis Summary: The combination therapy of reconstructive surgery and administration of oxygen therapy gave satisfactory results in both cases. Five sessions of hyperbaric treatment showed promising results. There is no infection, rapid wound healing, and cessation of flap compromise.